Chlamydial diversity and predictors of infection in a wild Australian parrot, the Crimson Rosella (Platycercus elegans). Issue 2 (14th July 2020) - Stokes, Helena S.; Martens, Johanne M.; Jelocnik, Martina; Walder, Ken; Segal, Yonatan; Berg, Mathew L.; Bennett, Andrew T. D.
Abstract: Members of the Chlamydia genus are known to cause disease in both humans and animals. A variety of other species in the order Chlamydiales are increasingly being discovered and emerging as potential pathogens, yet there are scarce data on the diversity, prevalence and impacts of these pathogens in wild birds. To address this gap, we investigated which Chlamydiales species are present in a wild population of a common Australian parrot, the Crimson Rosella ( Platycercus elegans ). We collected cloacal swabs and serum from 136 individuals in south‐eastern Australia, over two years, and tested several predictors of prevalence: age, sex, season and breeding status. We used multiple PCR assays to determine bacterial prevalence in cloacal swabs and a solid‐phase ELISA to determine seroprevalence. We found Chlamydiales PCR prevalence of 27.7% (95% CI 20.2, 36.2) and identified at least two families ( Chlamydiaceae and Parachlamydiaceae ). Regarding known chlamydial avian pathogens, we found C. psittaci at 6.2% (95% CI 2.7, 11.8) and C. gallinacea at 4.6% (95% CI 1.7, 9.8) prevalence. We also identified at least two potentially novel Chlamydiales species, of unknown pathogenicity. Sex and breeding status predicted Chlamydiales PCR prevalence, with females more likely to be infected than males, and non‐breeding birds more likely to be infected than breeding birds. Seroprevalence was 16% (95% CI 8.8, 25.9). Season and breeding status were strong predictors of seroprevalence, with highest seroprevalence in autumn and in non‐breeding birds. Our results reveal a diversity of Chlamydiales species in this abundant wild host, and indicate that host‐specific and temporal factors are associated with infection risk. Our findings suggest that wild parrots are a reservoir of both known and novel Chlamydiales lineages, of zoonotic and pathogenic potential.